The girl you left behind - Moyes, Jojo, 1969- (Pamela Dorman Books/Viking, 2013)
Unwillingly rendered an object of obsession by the Kommandant occupying her small French town in World War I, Sophie risks everything to reunite with her husband a century before a widowed Liv tests her resolve to claim ownership of Sophie's portrait.